2004
DOI: 10.1016/j.devcel.2004.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Retrotransposons Regulate Host Genes in Mouse Oocytes and Preimplantation Embryos

Abstract: A comprehensive analysis of transposable element (TE) expression in mammalian full-grown oocytes reveals that LTR class III retrotransposons make an unexpectedly high contribution to the maternal mRNA pool, which persists in cleavage stage embryos. The most abundant transcripts in the mouse oocyte are from the mouse transcript (MT) retrotransposon family, and expression of this and other TE families is developmentally regulated. Furthermore, TEs act as alternative promoters and first exons for a subset of host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
588
0
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 630 publications
(643 citation statements)
references
References 61 publications
34
588
0
9
Order By: Relevance
“…We propose that transcription on lateral loops often begins at adjacent active LTR promoters. Interestingly, activation of transcription from scattered LTR promoters in oocytes was recently shown in mammals, [65][66][67] thus implying evolutionary conservation of the transcription initiation mechanism during oogenesis.…”
Section: Widespread Transcription Of the Satellite Dna During The Lammentioning
confidence: 99%
“…We propose that transcription on lateral loops often begins at adjacent active LTR promoters. Interestingly, activation of transcription from scattered LTR promoters in oocytes was recently shown in mammals, [65][66][67] thus implying evolutionary conservation of the transcription initiation mechanism during oogenesis.…”
Section: Widespread Transcription Of the Satellite Dna During The Lammentioning
confidence: 99%
“…Although nothing is known about a potential NAIP stress response in the germ line, it has been demonstrated that NAIP mRNA and protein is upregulated in neurons following ischemic stress [64]. It is also interesting that activity of the human NAIP HERV-P LTR promoter is highest in testis, and, in general, ERVs are transcribed highly in germ cells and early embryogenesis compared to most normal somatic cells [32,65]. While there is no evidence that other IAP genes, with the exception of NAIP, use LTR promoters, the proposed upregulation may involve gene activation by nearby LTR enhancers, offering an explanation for the fact that LTR density upstream of IAP genes as a group is high compared to random genes.…”
Section: Discussionmentioning
confidence: 97%
“…An example is the carbonic anhydrase gene (CA1), where an ancestral LTR drives erythroid-specific expression of the orthologs [6]. The more commonly documented situation is where a lineage-specific LTR acts as a gene's promoter in one species but not the other, as illustrated by the b3GALT5 gene in human [31] and various mouse genes including Spindlin [32]. The results of this study illustrate a third evolutionary scenario not previously reported: distinct LTR elements specific to the primate or rodent lineages have independently assumed roles as promoters for the NAIP orthologs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, transposable elements serve as a dynamic reservoir of sequences for the evolution of gene function. In addition, mobile DNA has other important general functions, for example in chromosome structure and (epi)genetic regulation (Lyon 2000, Peaston et al 2004, Han & Boeke 2005, Slotkin & Martienssen 2007.…”
Section: Introductionmentioning
confidence: 99%